Williams gynecology - Hoffman, Barbara L.; Schorge, John O.; Halvorson, Lisa M.; Hamid, Cherine A.; Corton, Marlene M.; Schaffer, Joseph I. (McGraw-Hill, 2020)
"The only gynecological text to combine a medical reference and surgical procedural atlas in one beautifully illustrated volume - now updated and revised in a fourth edition"--
Keywords: gynekologie; gynecology; učebnice vysokých škol; textbooks (higher)